Faktor-Faktor dan Preferensi Pergerakan Pengguna Layanan Online Food Delivery Di Kota Bandung - Desiana, Renny; Hendarto, Syamsu Rizal; Miharja, Miming (Jurnal Perencanaan dan Pengembangan Kebijakan, 2025)
The advancement of information and communication technology has proliferated globally, as demonstrated by the emergence of various startups such as Gojek and Grab. Among the principal services provided by these enterprises is online food delivery, which facilitates the convenient ordering of food and beverages via mobile devices. This technological transformation not only influences patterns of human mobility but also shapes consumer preferences concerning the utilization of online food delivery services. This research employs descriptive analysis and logistic regression analysis as its methodological approach. The results indicate that preferences for using online food delivery services are determined not solely by socioeconomic factors and technological familiarity, but are also significantly influenced by social interactions and lifestyle considerations. Consequently, online food delivery services have not entirely supplanted the custom of dining in at restaurants; rather, they function as a complementary option that addresses the quotidian needs of consumers.